Poisoning during the COVID-19 pandemic and lockdown: retrospective analysis of exposures reported to the Poison Unit of the Mansoura Emergency Hospital. Issue 1 (31st December 2022) - Motawei, Shimaa M.; Shabka, Osama A.; Liu, Huimei
Abstract: Introduction: Coronavirus disease 2019 (COVID-19), originated in late December 2019, in Wuhan, China. The World Health Organization declared a pandemic on 11 March 2020, with the rapidly rising number of cases and fatalities over hours and days all around the world. Aim: To assess the number and the trend of the poisoning consultations to the Poison Unit in the Mansoura Emergency Hospital during the era of the COVID-19 pandemic in 2020. Methods: We collected data from the database of the Poison Unit and the Statistics Department of the Mansoura Emergency Hospital of the cases and the calls coming to the Poison Unit in the period from January 2018 through December 2020. We compared 2020 exposures to 2018–2019 exposures by using simple logistic models to provide effect size with odds ratios. Results: The Mansoura Emergency Hospital Poison Unit treated 1752 cases in 2020, compared to 2210 cases in 2018 and 2539 cases in 2019. The Poison Unit treated 26% fewer patients in 2020 than either 2018 or 2019), while calls increased nearly 50% in 2020 than in 2018 and 2019. Calls came more frequently from the general public than health professionals and more frequently in afternoon and evening than in the morning. There was a significant increase in the cases of pharmaceuticals ingestion, food poisoning, corrosives and households exposures in 2020 compared to 2018 and 2019 ( p- value 0.004, 0.024, and 0.0002, respectively; odds ratio 1.224, 1.691, and 1.692, respectively). Conclusion: The COVID-19 pandemic changed the pattern of poisoning exposure and use of the Poison Control Center services.